Possibilities of Using Artificial Intelligence in Security Analysis - Maciej Norbert Ciesielski (Journal of Modern Science)
Objectives The aim of the article is to present the characteristics and analytical potential of artificial intelligence in the area of ​​security analysis. The text is to help answer the following research questions: • What are the characteristics of analytical imagination identified as a tool that could be used by artificial intelligence in security analyses? • In what circumstances is artificial intelligence able to take into account the characteristics of the intelligence cycle in the generated answers and studies? • Which features of contextual thinking and critical thinking pose a challenge to artificial intelligence, and which are the field of its cognitive advantage over humans?